Global deletion of the immune cell transcription factor, T-bet, alters gut microbiota and insulin sensitivity in mice - Stolarczyk, E.; Vong, C. T.; Garrido-Mesa, N.; Marks, E.; Abdel-Aziz, D.; Ju, Q.; Jackson, I.; Powell, N.; Lord, G. M.; Howard, J. K. (Frontiers in Genetics, 2024)
The gut microbiota plays a role in energy homeostasis: its composition differs in lean and obese mice and may impact insulin sensitivity. The immune system has co-evolved with the gut microbiota, but direct regulation of microbial communities by the immune system and its metabolic impact is unclear. Mice lacking the immune cell specific transcription factor T-bet (Tbx21) are insulin sensitive. Compared with wild-type mice, T-bet deficient mice were found to have a higher proportion of colonic regulatory T cells despite significantly fewer colonic T cells, B cells and NK cells. Microbiota deletion by administration of antibiotics, increased colonic immune cell numbers. Furthermore, we report that T-bet−/− mice have an altered gut microbial composition and fecal short-chain fatty acid content, with an increase in butyrate production, compared with wild-type mice. Finally, in a proof-of concept study, we show that the enhanced insulin sensitivity observed in T-bet−/− mice is temporarily transmissible to antibiotic-treated wild-type mice through fecal transfer. Immune regulation of the gut microbiota by T-bet may be a novel pathway modulating insulin sensitivity.